Aspiration in the Context of Upper Gastrointestinal Endoscopy - A Thomson; J Tye-Din; S Tonga; J Scott; C Mclaren; P Pavli; F Lomas (Canadian Journal of Gastroenterology)
BACKGROUND: Pulmonary aspiration is a life-threatening complication of upper gastrointestinal endoscopy, the incidence of which has not been determined. Endoscopy-related aspiration has not been studied in procedures in which patients swallow a radiolabelled potential aspirate immediately before endoscopy and undergo nuclear scanning postprocedure.